Colanthelia longipetiolata (Poaceae: Bambusoideae), a new species of woody bamboo from the Brazilian Atlantic forest - de Jesus-Costa, Cristielle; Viana, Pedro L.; Clark, Lynn G.; Santos-Gonçalves, Ana Paula (Phytotaxa, 2019)
Colanthelia is a woody bamboo genus belonging to the Arthrostylidiinae and currently includes nine species. It can be recognized by a suite of morphological characters including hollow and thick-walled culms, branch complement with a promontory in the base and a dominant divergent branch bearing few to many secondary small branchlets from its base, culm leaves with a relatively well developed girdle and a crest or skirt at the juncture of the sheath and girdle, racemose or weakly paniculate synflorescences, and relatively long and narrow spikelets with visible rachilla internodes. During recent fieldwork in Minas Gerais state, a new species, Colanthelia longipetiolata, from the Brazilian Atlantic forest was collected, which is here described and illustrated. So far as we know, the species is endemic to the Caparaó National Park, in Minas Gerais state. Comments on its habitat, distribution and conservation status, a morphological comparison between C. longipetiolata and C. sparsiflora, and a revised identification key to all species of the genus are provided.